Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Aplikasi Quizizz terhadap Minat dan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas IV SD Inpres Bontomanai - Nurul Qalbi Ahmad; Rosleny Bab; Suardi Suardi (Journal on Education, 2024)
The main problem in this research is "is there an influence of the Problem Based Learning (PBL) learning model assisted by the Quizizz application on student interest and learning outcomes in the Class IV Social Sciences subject at SD Inpres Bontomanai". The aim of this research is to determine the effect of the problem based learning model assisted by the Quizizz application on student interest and learning outcomes in the Class IV Social Sciences subject at SD Inpres Bontomanai. This type of research is experimental research with a pre-experimental design approach. The research design is One-Group Pretest-Posttest. The data analysis techniques used are descriptive data analysis and inferential data analysis. The results of the descriptive analysis of students' interests and learning outcomes in the Class IV Social Sciences subject at SD Inpres Bontomanai using the problem based learning (PBL) learning model assisted by the Quizzizz application show an increase seen from the results of the students' pretest and posttest scores before and after implementing the problem based learning model. With the help of the Quizizz application, the results of inferential statistical analysis through the normality test showed that the pretest and posttest values ​​showed a result of 200 > 0.05, where H0 was rejected, so this data was normally distributed, while the hypothesis test using the paired sample t-test showed that the value was sig (2-tailed) equal to 0.000 < 0.05, it can be concluded that there is a real difference between student interest and learning outcomes seen from the pretest and posttest data. These results clearly show that there is an influence of the problem based learning (PBL) learning model assisted by the quizizz application. Therefore the alternative hypothesis H1 is accepted, while the hypothesis H0 is rejected.